Greenwashing and financial performance of firms: the moderating role of internal audit quality and digital technologies - Pupung Purnamasari; Indah Umiyati (Cogent Business & Management, 2024)
Greenwashing (GW) is a common business strategy employed by modern-day firms to realize sustainability and financial goals. However, the puzzle of whether GW and underlying conditions essential to improve the financial performance (FP) remains unresolved. This study aims to empirically investigate the impact of GW on FP by operationalizing internal audit quality and digital technologies as moderators. The data of non-financial Indonesian firms between 2018 to 2022 were drawn and analyzed using generalized method of moments (GMM) technique. The findings indicate that GW has a significant positive effect on FP. The results also confirmed a significant positive moderating effect of internal audit quality on the relationship between GW/FP whereas digital technologies exhibit an insignificant positive effect on the nexus between GW/FP. Our findings contribute to validating the implementation of GW blended with internal audit quality and digital technologies to improve the sustainability and financial portfolios of the firms located in emerging economies.
Keywords: 650; Greenwashing; financial performance; internal audit quality; digital technologies; environmental performance